APPLICATION EXPERIENCE OF CETIRIZINE IN THERAPY AGAINST ALLERGIC DERMATOSES AMONG CHILDREN - I.M. Korsunskaya; A.B. Zakharova; E.V. Zhavoronkova; S.S. Zelentsova; Z. Nevozinskaya ("Paediatrician" Publishers LLC, 2007)
The authors highlight the application experience of cetirizine (Parlazin, Egis, Hungary) among 27 children aged between 3 and 17 years, suffering from hives, allergic dermatitis (common and contact), atopic dermatitis and associated respiratory allergy presentations. They showed the clinical efficiency of a medication and its good tolerance.Key words: cetirizine, allergic dermatitis, atopic dermatitis, children, treatment.